-8(-8x-6)=-6x-222

Simple and best practice solution for -8(-8x-6)=-6x-222 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(-8x-6)=-6x-222 equation:


Simplifying
-8(-8x + -6) = -6x + -222

Reorder the terms:
-8(-6 + -8x) = -6x + -222
(-6 * -8 + -8x * -8) = -6x + -222
(48 + 64x) = -6x + -222

Reorder the terms:
48 + 64x = -222 + -6x

Solving
48 + 64x = -222 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
48 + 64x + 6x = -222 + -6x + 6x

Combine like terms: 64x + 6x = 70x
48 + 70x = -222 + -6x + 6x

Combine like terms: -6x + 6x = 0
48 + 70x = -222 + 0
48 + 70x = -222

Add '-48' to each side of the equation.
48 + -48 + 70x = -222 + -48

Combine like terms: 48 + -48 = 0
0 + 70x = -222 + -48
70x = -222 + -48

Combine like terms: -222 + -48 = -270
70x = -270

Divide each side by '70'.
x = -3.857142857

Simplifying
x = -3.857142857

See similar equations:

| s+7(4)=16 | | 193=3+10p | | -3(-3+y)+3y=4 | | -5m=-85 | | -7(x+4)=0 | | 6n-2(3-n)=-13 | | 44+2c=7c-6 | | x/13=-7 | | 3x+3/3= | | 6(2m-1)-1(11m+6)=7 | | 7x-11=17-7x | | 60-2m=8m | | 7+14=16 | | 6x-7+3x=10+9x-7 | | 13=3x-6 | | 3-10+1-5= | | y=z+x-8/w | | 14=p/2 | | 4z=2.5+2.7 | | 27=0.5x(2+7) | | 9-1/2b=5+8/2b | | xx=42 | | 4k^2-13k+3=0 | | 8-(4y-9)=5-5y | | -3x+22/2= | | (x-1/2)=(2-x/3) | | 5.4/-4.5y | | -10?4(3p?10)=18 | | -3x+9+3x=4 | | .2(5+2x)=4(.3x+.9) | | 4c=4 | | 64b^4+3b=0 |

Equations solver categories